O filosofo crítico é um gênio - Cecchinato, Giorgia (Studia Kantiana, 2023)
This article intends to show first that the systematic demands placed in the Preface to Criticism of the faculty of judging impose a restriction on the concept of genius to artistic activity; second, it provides an interpretation of the complementarity of the receptive moment and the creative moment in the case of the work of art. In the concluding part, it brings together some characteristics of genius to the critical philosopher on the basis of some significant analogies: the legislative activity of genius and that of reason, the analogy with the function of making a technical activity compatible with an organic vision and the necessary complementarity between receptive and creative / communicative moments in art and philosophy.